2021
DOI: 10.22207/jpam.15.3.17
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Probiotics on Various Diseases and their Therapeutic Role: An Update Review

Abstract: Probiotic bacteria play a critical and functional role in clinical and nutritional applications. In the present study, the ability of various probiotics and their metabolites in the prevention and treatment of different diseases, infections and disorders was reviewed. The issues that were noticed are included: Fibrocystic, diabetes, acne, colon cancer, cardiovascular, urinary tract infections, atopic eczema syndrome, food allergies and obesity. Enhancement in using drug treatment has led to the appearance of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 134 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…The bacterial strains used in probiotics help in Cholesterol lowering and its metabolism (Stavropoulou et al, 2020), colonization in the intestinal, respiratory and urogenital tracts, inhibition of the carcinogenesis, directly or/and indirectly, via the stimulation of the immune system, the metabolism of lactose, the absorption of calcium and the potential of vitamin synthesis. Probiotics also produces many useful metabolites during their growth and metabolism (Stavropoulou et al, 2020;Hashempour-et al, 2021) e.g. production of bioactive compounds, conjugated linolenic acid, propionic acid, etc (Guillot et al, 2003).…”
Section: Sources Of Probiotic Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterial strains used in probiotics help in Cholesterol lowering and its metabolism (Stavropoulou et al, 2020), colonization in the intestinal, respiratory and urogenital tracts, inhibition of the carcinogenesis, directly or/and indirectly, via the stimulation of the immune system, the metabolism of lactose, the absorption of calcium and the potential of vitamin synthesis. Probiotics also produces many useful metabolites during their growth and metabolism (Stavropoulou et al, 2020;Hashempour-et al, 2021) e.g. production of bioactive compounds, conjugated linolenic acid, propionic acid, etc (Guillot et al, 2003).…”
Section: Sources Of Probiotic Strainsmentioning
confidence: 99%
“…Some of these bacteria are known as probiotic which addition to digestion aid, produce complex compounds such as vitamins and antibiotics and can be helpful for the body. World Health Organization (WHO), reported that there are four group of complications in patients with medical conditions, which are: Systemic infections, detrimental metabolic activity, overstimulation of immunocompromised individuals, and gene transfer (Hashempour et al, 2021). Some of disorders side effects have been reported in the gastrointestinal tract, such as vomiting, nausea, spasms, diarrhea, bloating, thirst, and taste disturbances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics are known to have beneficial effects on human health by forming a healthy microbiome and improving intestinal barrier function in the human intestine [13]. Recently, probiotics had various beneficial effects, such as preventing respiratory viruses, including COVID-19, anti-allergy, improvement of metabolic disease, and anti-inflammation on the skin [14][15][16]. Among the probiotic species, Lactocaseibacillus rhamnosus, Bifidobacterium breve, and Escherichia coli Nissle 1917 have been reported to prevent inflammation in a COPD mouse model but have not been studied in other species [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are well-known to improve the intestinal environment and recently, their beneficial effects on human health are extended to improve various diseases, for instance, type 2 diabetes, non-alcoholic fatty acid disease, and atopic dermatitis [16,17]. The beneficial effects of probiotics on the immune system and gut-bone axis have been recently reported, and probiotics have received considerable attention for treating autoimmune diseases such as RA [18,19].…”
Section: Introductionmentioning
confidence: 99%